EFFECTIVENESS OF GROUP GUIDANCE SERVICES WITH DISPUTING IRRATIONAL BELIEF TECHNIQUE ON FATHERLESS CHILDREN'S EMOTION REGULATION - Mahisani, Tiara Putri; Rusman, Abdul Aziz (FORUM PAEDAGOGIK, 2025)
This study aims to determine the effectiveness of group counseling services using the Disputing Irrational Beliefs technique on emotion regulation of fatherless children at the Aceh Sepakat Orphanage. The research employs a quantitative approach with a one-group pretest-posttest design pre-experimental type. The subjects of this study were 18 fatherless children who experienced difficulties in emotion regulation, all of whom were used as samples through saturated sampling technique. The intervention was conducted in four sessions of group counseling services using the DIB technique, which consists of empirical, logical, and pragmatic discussing stages. Data collection was performed using an emotion regulation questionnaire adopted from previous research, with validity and reliability tested in earlier studies. The data were analyzed using the Wilcoxon signed Rank Test. The analysis results showed an Asymp. Sig. (2-tailed) value of 0.001 0.05, indicating a significant difference between the pretest and posttest scores. Thus, it can be concluded that group guidance services using the technique of disputing irrational beliefs are effective in improving the emotional regulation skills of fatherless children. This study provides important contributions as an educational-based psychological intervention to help children who experience the loss of a father figure in managing their emotions more adaptively.